Health Status and Labour Force Participation: Evidence from the HILDA Data - Kalb, G; Cai, L (My University, 2004)
Although the overseas literature on the effect of health on labour force participation is extensive, especially in the US, the literature in an Australian context is scarce. This paper contributes to the understanding of this issue using the recently released Household, Income and Labour Dynamics in Australia (HILDA) Survey data. The potential endogeneity of the health variables, especially self-assessed health, in the labour force participation equation is addressed by estimating the health equation and the labour force participation equation simultaneously. We also take into account the correlation between the error terms in the two equations to obtain an efficient result. The null-hypothesis of exogeneity of health to labour force participation is tested based on a test of the joint significance of the labour force participation variable in the health equation and the correlation coefficient of the two error terms. The estimation is conducted separately for males aged 15 to 49, males aged 50 to 64, females aged 15 to 49 and females aged 50 to 60. The results indicate that better health increases the probability of labour force participation for all four groups. As for the feedback effect, it is found that labour force participation has a significant positive impact on older females’ health, and a significant negative effect on younger males’ health. For younger females and older males, the impact of labour force participation on health is not significant. Based on the joint test, the exogeneity hypothesis is rejected for all four groups.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Melbourne Institute Working Papers
Keywords: Health; Employment; Employment -- Labour force participation; Health and wellbeing; Labour market; Health; Employment and unemployment